Nanomaterial-based reactive oxygen species scavengers for osteoarthritis therapy. (May 2023) - Zhang, Shiyong; Wang, Liying; Kang, Yunze; Wu, Jun; Zhang, Ziji
Abstract: Reactive oxygen species (ROS) play distinct but important roles in physiological and pathophysiological processes. Recent studies on osteoarthritis (OA) have suggested that ROS plays a crucial role in its development and progression, serving as key mediators in the degradation of the extracellular matrix, mitochondrial dysfunction, chondrocyte apoptosis, and OA progression. With the continuous development of nanomaterial technology, the ROS-scavenging ability and antioxidant effects of nanomaterials are being explored, with promising results already achieved in OA treatment. However, current research on nanomaterials as ROS scavengers for OA is relatively non-uniform and includes both inorganic and functionalized organic nanomaterials. Although the therapeutic efficacy of nanomaterials has been reported to be conclusive, there is still no uniformity in the timing and potential of their use in clinical practice. This paper reviews the nanomaterials currently used as ROS scavengers for OA treatment, along with their mechanisms of action, with the aim of providing a reference and direction for similar studies, and ultimately promoting the early clinical use of nanomaterials for OA treatment. Statement of significance: Reactive oxygen species (ROS) play an important role in the pathogenesis of osteoarthritis (OA). Nanomaterials serving as promising ROS scavengers have gained increasing attention in recent years. This review provides a comprehensive overview of ROS production and regulation, as well as their role in OA pathogenesis. Furthermore, this review highlights the applications of various types of nanomaterials as ROS scavengers in OA treatment and their mechanisms of action. Finally, the challenges and future prospects of nanomaterial-based ROS scavengers in OA therapy are discussed. Graphical abstract: Image, graphical abstract